Edukasi Tentang Aromatherapi Lemon (Citrus Lemon) Terhadap Mual dan Muntah Pada Ibu Hamil di Desa Air Joman Kisaran - Pohan, Atika; Umamy, Farida; Tamara, Cindy; Ramadani, Nurhidayah (Cattleya Darmaya Fortuna, 2022)
Pregnancy is a physiological part of a woman's life. This process causes physical, mental and social changes which are influenced by several physical, psychological, environmental, socio-cultural and economic factors. And pregnancy also causes changes in all systems in the mother's body, including the endocrine and gastro intestinal systems, causing various discomfort or physiological complaints such as complaints of nausea and vomiting. Pregnancy is a very meaningful experience for women, families and society. (Muliatul Jannah, 2021). Nausea and vomiting (emesis gravidarum) are one of the earliest, most common and most stressful symptoms associated with pregnancy. However, obstetricians and general practitioners consider nausea and vomiting to be merely a physiological symptom, and a problem that people often feel powerless to help overcome. Nausea and vomiting are often ignored because they are considered a normal consequence in early pregnancy without knowing the great impact it has on the woman and her family (Tiran. D, 2019).